Symbolic and quantitative approaches to reasoning with uncertainty 11th European conference, ECSQARU 2011, Belfast, UK, June 29-July 1, 2011. Proceedings - Liu, Weiru; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 11th European Conference on Symbolic and Quantitative Approaches to Reasoning with Uncertainty, ECSQARU 2011, held in Belfast, UK, in June/July 2011. The 60 revised full papers presented together with 3 invited talks were carefully reviewed and selected from 108 submissions.  The papers are organized in topical sections on argumentation; Bayesian networks and causal networks; belief functions; belief revision and inconsistency handling; classification and clustering; default reasoning and logics for reasoning under uncertainty; foundations  of reasoning and decision making under uncertainty;  fuzzy sets and fuzzy logic; implementation and applications of uncertain systems; possibility theory and possibilistic logic; and uncertainty in database
Electronic reproduction.
Keywords: Electronic books; Computer science; Logic design; Information storage and retrieval systems; Information systems; Artificial intelligence